Веб-сайт як засіб комунікативної діяльності органів студентського самоврядування - Дихтярук, Уляна; Вовк, Наталія (Видавництво Львівської політехніки, 2020)
Involvement of youth in student selfgovernment significantly contributes to the development of such traits as: responsibility, independence, respect, tolerance, respect for oneself and others, dedication to their work, creativity, need for self-development, etc. Also, involvement of youth in participation in activities Student selfgovernment bodies facilitate future specialists to gain experience, be ready for informed participation in society.
Keywords: органи студентського самоврядування (ООС); громадська організація; інформація; соціальні мережі; вебсайт; заклад вищої освіти